‘Word play’ as an instrument for creating comic effects (based on Tom Sharp’s novels) - A. A. Kharkovskaya; K. A. Chekhova (Вестник Самарского университета: История, педагогика, филология, 2021)
Various approaches to theoretical interpretation of the concept word play are considered in the present article. The research project is aimed at describing the nature of the phenomenon mentioned above and summing up various means and ways of its verbal implementation within the genre of a comic novel. At the initial stage of the article there is an attempt to find the most frequently applied verbal markers of the concept play in reference to stylistic and philosophical aspects of the phenomenon while the next step is devoted to the analysis of specific language means for creating a comic effect in the textual space of novels. The attention is focused upon identification of the most frequently applied strategies for creating word play effects within a comic novel. Our research is based on the novels written by a well-known modern English satirist Tom Sharp (Porterhouse Blue Blott on the Landscape). The results obtained contribute to the adequate interpretation of a large variety of language means and devices used by the author for creating comic effects. Besides the word play role in intensifying the comic effects is also shown (at the lexical level they comprise the so-called speaking names represented by toponyms, a number of the individual author's puns in the format of a dialogue, the deformation of phraseological units and the similar language units. The most frequent language means applied by the author include the characterological names and comic dialogues with puns incorporated. The novelty of our work is provided by the unique character of the language material on the one hand and by the introduction of some erotic motives reflecting modern trends in literature free from strict censorship, on the other.